A COF-like conductive conjugated microporous poly(aniline) serving as a current collector modifier for high-performance Li–S batteries. Issue 3 (20th December 2021) - Chen, Xin; Wang, Yubing; Wang, Jianan; Liu, Jianwei; Sun, Shiyi; Zhu, Lei; Ma, Qianyue; Zhu, Ningrui; Wang, Xi; Chen, Jie; Yan, Wei
Abstract : A COF-like CMPA was synthesized by the B–H coupling reaction, serving as the functional layer of the current collector in the sulfur cathode. Benefiting from the advantages of CMPA, the cathode achieved long-life cyclability and high energy density. Abstract : Conducting polymers such as polyaniline have demonstrated their considerable superiorities when serving as promising sulfur host materials for Li–S batteries, owing to their strong affinity for lithium polysulfides (LiPSs) and excellent conductivity. However, less polar groups, an unstable frame structure and low specific surface area limited their electrochemical performance. Herein, a covalent organic framework (COF)-like conjugated microporous polyaniline (CMPA) with an extended π-conjugated system and permanent 3D microporosity was developed as a modified material for use in the current collector of the sulfur cathode for highly efficient Li–S batteries. This multifunctional CMPA shows the integrated nature of conjugated microporous polymers (CMPs) and PANi, ensuring exceptionally specific surface area, nitrogen-rich character, stable framework and high conductivity. Owing to these superiorities, the current collector modified by CMPA delivers a high areal capacity (7.42 mA h cm −2 ) and high energy density (202.8 W h kgcell −1 ) even under a sulfur loading of 8.72 mg cm −2 . These outcomes present a new strategy for designing advanced cathodes and also demonstrate the potential of CMPs in energy storage batteries.